Agricultural Development in Asia and Africa Essays in Honor of Keijiro Otsuka - Estudillo, Jonna P.; Kijima, Yoko; Sonobe, Tetsushi (Emerging-Economy State and International Policy Studies, 2023)
This Open Access book explores the multifaceted nature of agricultural and rural development in Asia and examines the extent to which the Asian experience is being replicated in contemporary Africa. This volume compiles the works of top scholars who provided analyses and evidences from household-level surveys collected for many years in several parts of Asia and Africa. The most important finding presented in this book is that African agricultural development has evolved following the pathways of Asian agricultural development. The common pathways are borrowed technology from abroad and adaptive research in rice farming; secured property rights on natural resources; adoption of ICTs; investments in human capital, including training; and launching of the high-value agriculture. In both continents, agricultural development started in the crop sector, which had a strong tendency to induce the dynamic development of other sectors in rural areas.